2020
DOI: 10.1002/ece3.6704
|View full text |Cite
|
Sign up to set email alerts
|

Are movements of daytime and nighttime passerine migrants as different as day and night?

Abstract: Even after decades of research, the migration of songbirds still holds numerous secrets. Distinct stopover and routing behavior of diurnally and nocturnally migrating songbirds has been stated in the 1960s, but empirical confirmation is yet lacking widely. We studied the behavior of individual diurnally migrating dunnocks and nocturnally migrating blackcaps by means of large‐scale automated radio‐telemetry. Birds were radio‐tagged during their stopover at the German North Sea coast. Our data indicate longer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 94 publications
1
9
0
Order By: Relevance
“…This finding is especially interesting as all except one of the species investigated here are mainly nocturnal migrants, which have often been described to be less sensitive to the overflown landscape as compared to diurnal migrants (Lack 1963;Eastwood 1967;Bruderer and Liechti 1998;Diehl et al 2003). The coastlines still seem to have a leading line effect for nocturnal migrants, too (Buurma 1995;Brust et al 2019;Michalik et al 2020), which has also been observed in other regions (Richardson 1978).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…This finding is especially interesting as all except one of the species investigated here are mainly nocturnal migrants, which have often been described to be less sensitive to the overflown landscape as compared to diurnal migrants (Lack 1963;Eastwood 1967;Bruderer and Liechti 1998;Diehl et al 2003). The coastlines still seem to have a leading line effect for nocturnal migrants, too (Buurma 1995;Brust et al 2019;Michalik et al 2020), which has also been observed in other regions (Richardson 1978).…”
Section: Discussionsupporting
confidence: 68%
“…west of 8.08° E (Fig. 1), it had most likely migrated offshore (Brust et al 2019;Michalik et al 2020). 'Arrivals' further east, at the southern North Sea coast, i.e.…”
Section: Analyses Of Radio-telemetry Datamentioning
confidence: 99%
See 2 more Smart Citations
“…As the diurnal E. balteatus thus adopts night-time migration in a similar way as certain dragonfly or beetle species (Feng et al, 2006; Anderson, 2009), our work shines new light on the migration strategies of these globally important beneficial insects. As such, certain hoverfly species likely possess specific behavioral traits to undertake both nocturnal and diurnal migration (Michalik et al, 2020). Given the major ecological implications of such ‘dual’ migration strategy e.g., in terms of pollination or pest control, this knowledge gap urgently needs to be filled.…”
Section: Discussionmentioning
confidence: 99%